Does Board Size Really Matter? Evidence from Australia - Lukas Y. Setia-Atmaja (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This study examines the impact of board size of Australian firms on Tobin’s Q. Agency theory suggests that there is an inverse relationship between board size and Tobin’s Q (Yermack 1996; Eisenberg et al. 1998). The resource dependence argument, however, hypothesizes that larger boards can lead to higher performance as the CEO’s need for advice is a function of the complexity of the organization (Pfeffer 1972; Klein 1998). Analyzing a panel data of 1,530 firm-year observations using random effects technique, this study finds a positive relationship between board size and Tobin’s Q. The random effects regression results also reveal that the positive relationship between board size and Tobin’s Q is driven by firm size as this positive relationship is only found in larger firm sample but not in the smaller firm sample. The overall results support the resource dependence argument.